Embedded solitons with χ(2) and χ(3) nonlinear susceptibilities having multiplicative white noise via Itô Calculus. (September 2022) - Zayed, Elsayed M.E.; Alngar, Mohamed E.M.; Shohib, Reham M.A.; Biswas, Anjan; Yıldırım, Yakup; Moraru, Luminita; Mereuta, Elena; Alshehri, Hashim M.
Abstract: The objective of this paper is to locate the embedded solitons with χ ( 2 ) and χ ( 3 ) nonlinear susceptibilities in presence of multiplicative noise. Itô Calculus was implemented to carry out the analysis of the corresponding stochastic differential equation. The unified Riccati equation expansion method and enhanced Kudryashov's approach yielded dark, bright and singular solitons. The derived soliton solutions show that the effect of white noise is present only in the phase component. Highlights: This paper recovered for the first time embedded solitons with χ ( 2 ) and χ ( 3 ) nonlinear susceptibilities in presence of multiplicative white noise by the usage of Itô Calculus. The unified Riccati equation expansion method and the enhanced Kudryashov's approach gave way to such solitons. The effect of white noise appeared only in the phase component of the solitons.